Factors influencing attitudes towards euthanasia and abortion among medical students at a university in Peru - Ponce-Pantigoso, Mercedes (2024)
Introduction. The ethical debate surrounding euthanasia and abortion is relevant both in the medical and moral spheres. In the Peruvian context, these practices face legal and ethical challenges. Objective. To analyze the attitudes of medical students towards euthanasia and abortion, considering sociodemographic, academic, and religiosity variables. Methods. A descriptive, cross-sectional, and correlational study was conducted with medical students from a private university in Peru. Online questionnaires were administered to assess attitudes towards euthanasia and abortion, as well as religiosity and sociodemographic characteristics. Results. 341 participants were evaluated. Regarding attitudes towards abortion, religiosity (β = 0.314, p < 0.001), female gender (β = -0.243, p < 0.001), clinical/surgical years (β = -0,190, p < 0.001), and employment (β = 0,111, p = 0.026) were associated. As for attitudes towards euthanasia, associations were observed with religiosity (β = -0.234, p < 0.001) and female gender (β = 0.108, p = 0.042). Conclusions. The influence of religiosity and gender on medical students' attitudes towards euthanasia and abortion is highlighted. These findings have implications for medical education and ethical understanding in a context where these practices face legal and social challenges.